Breaking Boundaries: A Comprehensive Review of Screenless Display Technology - Monali Suresh Gulhane; Sushil Bakhtar (International Journal of Optical Innovations & Research, 2024)
This review explores new ways of showing images without traditional screens. We cover technologies like holography, where images appear to float in space, and retinal projection, which projects images directly onto your eye. We also discuss virtual retinal displays, which draw images on your retina using lasers, and augmented reality (AR), which overlays digital content onto your real-world view.Visual picture, Synaptic interface, Virtual Retinal Display. This primarily elucidates and illustrates the operation of screen-less screens and their scientific uses. A revolution in the field of displays and large, expensive displays that are hard to control power supply and limitations would result from this reality. It is also a well-developed, useful invention. By utilizing Ravebot technology, this essay emphasizes the ingenuity and potential significance of screenless displays. Screenless displays provide an answer to the drawbacks of standard displays, including their expensive price, bulkiness, and limited power usage. Screenless screens offer great degrees of privacy and can do away with bulky hardware, which might completely change the display technology landscape.A major factor in the successful operation of screenless displays is ravebot technology. Because of its implementation, which improves privacy and lessens the need for large hardware, it is a desirable option for a variety of applications. Furthermore, continuing patent discoveries point to this new technology's potential for broad acceptance as well as its continued advancement. This technique would revolutionize the sector of expensive, large panels and monitors, which have proven to be challenging to handle in terms of power consumption and restrictions. In summary, screenless displays enabled by Ravebot technology are a huge innovation that has the potential to completely change the market for monitors and displays by providing more effective and manageable substitutes for current systems.
Keywords: Hologram; retinal direct; synaptic interface; visual image